2022
DOI: 10.1002/path.5891
|View full text |Cite
|
Sign up to set email alerts
|

Genomic catastrophe, the peritoneal cavity and ovarian cancer prevention

Abstract: The current theory of carcinogenesis for the deadliest of ‘ovarian’ cancers—high‐grade serous carcinoma (HGSC)—holds that the malignancy develops first in the fallopian tube and spreads to the ovaries, peritoneum, and/or regional lymph nodes. This is based primarily on the observation of early forms of serous neoplasia (serous tubal intraepithelial lesions [STILs], and serous tubal intraepithelial carcinomas [STICS]) in the fimbria of women undergoing risk reduction surgery. However, these lesions are uncommon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…These include: (1) ovarian inclusion cysts, which contain tubal epithelium that could undergo the same morphological changes as the epithelium located in the fallopian tubes, and thus lead to ovarian cancer (2) the previously mentioned precursor escape model, combined with genomic catastrophe, which means a STIC suddenly develops with invasive and metastatic potential (3) sampling error or underdiagnosis of STIC. The validity and clinical relevance of these theories are currently unknown, but they might have implications for the safety of RRS with DO [49,61,62].…”
Section: Risk-reducing Salpingectomy With Delayed Oophorectomymentioning
confidence: 99%
“…These include: (1) ovarian inclusion cysts, which contain tubal epithelium that could undergo the same morphological changes as the epithelium located in the fallopian tubes, and thus lead to ovarian cancer (2) the previously mentioned precursor escape model, combined with genomic catastrophe, which means a STIC suddenly develops with invasive and metastatic potential (3) sampling error or underdiagnosis of STIC. The validity and clinical relevance of these theories are currently unknown, but they might have implications for the safety of RRS with DO [49,61,62].…”
Section: Risk-reducing Salpingectomy With Delayed Oophorectomymentioning
confidence: 99%
“…Most OV patients are resistant to platinum-based chemotherapy, resulting in increased mortality. Platinum resistance in OV is driven by transcriptome and tumor heterogeneity [ 3 ]. A previous study has shown that ovarian cancer stem cells (OCSCs), which are chemoresistant and responsible for disease recurrence and relapse, are enriched by platinum-based chemotherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%